2009
DOI: 10.4137/pri.s2799
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of an Adjacent Methionine Residue Inhibits Regulatory Seryl-Phosphorylation of Pyruvate Dehydrogenase

Abstract: Abstract:A Met residue is located adjacent to phosphorylation site 1 in the sequences of mitochondrial pyruvate dehydrogenase E1α subunits. When synthetic peptides including site 1 were treated with H 2 O 2 , the Met residue was oxidized to methionine sulfoxide (MetSO), and the peptides were no longer phosphorylated by E1α-kinase. Isolated mitochondria were incubated under state III or IV conditions, lysed, the pyruvate dehydrogenase complex (PDC) immunoprecipitated, and tryptic peptides analyzed by MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In addition to the direct effect on protein function, methionine sulfoxidation has been recently postulated as a mechanism to couple oxidative signals to changes in protein phosphorylation. This hypothesis derives from studies on two unrelated plant enzymes, mitochondrial pyruvate dehydrogenase20 and cytoplasmic nitrate reductase19, both of which have a methionine residue proximal to a regulatory phosphorylation site. In both cases, the authors demonstrated that the oxidation of these methionine residues resulted in the inhibition of phosphorylation, suggesting that the oxidation status of these methionines allows the enzymes to monitor oxidative stress and subsequently code this information in terms of phosphorylation patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the direct effect on protein function, methionine sulfoxidation has been recently postulated as a mechanism to couple oxidative signals to changes in protein phosphorylation. This hypothesis derives from studies on two unrelated plant enzymes, mitochondrial pyruvate dehydrogenase20 and cytoplasmic nitrate reductase19, both of which have a methionine residue proximal to a regulatory phosphorylation site. In both cases, the authors demonstrated that the oxidation of these methionine residues resulted in the inhibition of phosphorylation, suggesting that the oxidation status of these methionines allows the enzymes to monitor oxidative stress and subsequently code this information in terms of phosphorylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the activities of calcineurin, a protein phosphatase, as well as Ca 2+ /calmodulin-dependent protein kinase II, have been previously shown to be modulated by specific methionine oxidation1718. Furthermore, it has been reported that the oxidation of methionine residues within the phosphorylation motif of nitrate reductase19 and pyruvate dehydrogenase20 inhibits the phosphorylation of nearby sites, providing a mechanism to couple oxidative signals to changes in protein phosphorylation. These isolated observations imply that reversible methionine oxidation might serve as a rheostat to control the phosphorylation of proximal phospho-acceptors21.…”
mentioning
confidence: 99%
“…Oxidation of the +4 Met residue, which serves as a hydrophobic recognition element for the kinase, markedly inhibited phosphorylation. In a related study, also using synthetic peptides and a recombinant kinase, Miernyk et al (2009) observed that oxidation of the +1 Met of pyruvate dehydrogenase (PDH) strongly inhibited phosphorylation of the adjacent Ser residue.…”
Section: Crosstalk Between Met Oxidation and O-phosphorylationmentioning
confidence: 99%
“…However, the common occurrence of Met adjacent to Ser/ Thr/Tyr residues (Rao et al 2013) and the frequent occurrence of MetSO (Ghesquière et al 2011;Liu et al 2013;Salvato et al 2014) near O-phosphorylation-sites (Song et al 2012) suggests that crosstalk between these two PTM's is widespread. (Hardin et al 2009;Miernyk et al 2009), oxidation of Met might directly inhibit O-phosphorylation of a nearby Ser/Thr/Tyr-residue by interfering with the kinase recognition/binding (Fig. 1).…”
Section: Crosstalk Between Met Oxidation and O-phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation